(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Nikolaev S.G. Keywords: bilingualism, conceptualization, linguistic accomplishments, sociology, cognitology, pragmatics, psychology, theory of literary texts and translation, history of communication. This article is a substantiation of the necessity for profound integrative conceptualization of bilingualism in the world of today. The said conceptualization should rely on recent linguistic accomplishments and be carried out at the junction of the sciences allied with linguistics: sociology, cognitology, pragmatics, psychology, theory of literary texts, translation and history of communication.